1974
DOI: 10.1063/1.1680939
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo classical dynamical study of the Cl + Cl2 and I + I2 systems: Vibrational relaxation and atom-exchange reactions

Abstract: Articles you may be interested inEffects of translational, rotational, and vibrational energy on the dynamics of the D+H2 exchange reaction. A classical trajectory study J. Chem. Phys. 94, 7991 (1991); 10.1063/1.460133 Vibrational relaxation of Cl2 by HCl and DCl and selfrelaxation of HCl and DCl: A Monte Carlo quasiclassical trajectory study J. Chem. Phys. 66, 2545 (1977); 10.1063/1.434250On the thermal rate coefficient and activation energy of the I+I2 atomexchange reactionThe Monte Carlo quasiclassical traj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 42 publications
(1 reference statement)
2
3
0
Order By: Relevance
“…Similar values, 2968 and 2666 K, respectively, were obtained by Thompson [21] from the Monte Carlo trajectory calculations, and by Bunker and Davidson [22] from thermodynamic considerations. Geometrical average of the potential well depths obtained by Thompson and by Bunker and Davidson gives c, /k =2813 K. The studies of Blake and Burns [20] and of Thompson [21] suggest that Lennard-Jones potential with parameters discussed above is an acceptable approximation of the overall forces dominating the I+I2 interaction, even though it ignores such effects as, for example, the AD (r ) =g, exp[a( r, *r ) ], Therefore the values of hD for the Ar-N2 interactions were obtained from the formula (55). Parameters for the interaction potentials for the Ar-N2 system were taken from Ref.…”
Section: Introductionsupporting
confidence: 81%
“…Similar values, 2968 and 2666 K, respectively, were obtained by Thompson [21] from the Monte Carlo trajectory calculations, and by Bunker and Davidson [22] from thermodynamic considerations. Geometrical average of the potential well depths obtained by Thompson and by Bunker and Davidson gives c, /k =2813 K. The studies of Blake and Burns [20] and of Thompson [21] suggest that Lennard-Jones potential with parameters discussed above is an acceptable approximation of the overall forces dominating the I+I2 interaction, even though it ignores such effects as, for example, the AD (r ) =g, exp[a( r, *r ) ], Therefore the values of hD for the Ar-N2 interactions were obtained from the formula (55). Parameters for the interaction potentials for the Ar-N2 system were taken from Ref.…”
Section: Introductionsupporting
confidence: 81%
“…[17][18][19][20][21][22][23] Emission spectra attributable to Cl 3 were observed by Kawasaki et al 14 and Wright et al 15 These data were in reasonable agreement with each other. An IR spectrum of Cl 3 in a Kr matrix was reported by Nelson and Pimentel.…”
Section: Introductionsupporting
confidence: 80%
“…Following this work, Wright et al suggested that a 370−420 nm emission band, observed when Cl 2 was photodissociated under relatively high-pressure conditions, might also originate from Cl 3 . In parallel with the experimental efforts there have been many attempts to calculate potential energy surfaces for trihalogens using ab-initio , and semiempirical methods. , …”
Section: Introductionmentioning
confidence: 99%